The Reproducibility of Nuclear Morphometric Measurements in Invasive Breast Carcinoma - Pauliina Kronqvist; Teijo Kuopio; Yrjö Collan; Csaba Horvath; Ülle Tamm (Analytical Cellular Pathology)
The intraobserver and interobserver reproducibility of computerized nuclear morphometry was determined in repeated measurements of 212 samples of invasive breast cancer. The influence of biological variation and the selection of the measurement area was also tested. Morphometrically determined mean nuclear profile area (Pearson’s r 0.89, grading efficiency (GE) 0.95) and standard deviation (SD) of nuclear profile area (Pearson’s r 0.84, GE 0.89) showed high reproducibility. In this respect, nuclear morphometry equals with other established methods of quantitative pathology and exceeds the results of subjective grading of nuclear atypia in invasive breast cancer. A training period of eight days was sufficient to produce clear improvement in consistency of nuclear morphometry results. By estimating the sources of variation it could be shown that the variation associated with the measurement procedure itself is small. Instead, sample associated variation is responsible for the majority of variation in the measurements (82.9% in mean nuclear profile area and 65.9% in SD of nuclear profile area). This study points out that when standardized methods are applied computerized morphometry is a reproducible and reliable method of assessing nuclear atypia in invasive breast cancer. For further improvement special emphasize should be put on sampling rules of selecting the microscope fields and measurement areas.